Cyberagresja w szkole – wyzwania dla nauczycieli - Bartkowicz, Zdzisław; Chudnicki, Andrzej (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Z eskalacją cyberagresji stosowanej przez uczniów szkoły usiłują radzić sobie poprzez restrykcje, a nawet „wojnę”, powodując tym nakręcanie spirali przemocy. Tymczasem skuteczne przeciwdziałanie cyberagresji jest możliwe środkami typowo edukacyjnymi, czyli kształtując empatię i inne sprawności stanowiące przeciwwagę dla antyspołecznego zachowania. Wskazano na rolę szkoły w uczeniu odpowiedzialnego, zsocjalizowanego korzystania ze środków elektronicznej komunikacji.

Schools attempt to manage with the escalation of the electronic aggression applied by pupils, across restrictions and the war, causing this winding up of the spiral of the violence. The however effective counteraction of the electronic aggression is possible through the use of typical educational manners, that is increasing the empathic sensibility and other prosocial efficiencies counterpoising for the antisocial behaviour. The importance of the school in the teaching of the responsible, socialized use from devices of the electronic communication was discussed.
Cyberaggression at School – Challenges for Teachers
Keywords: cyberagresja; cyberbullying; netykieta; profilaktyka agresji elektronicznej; karanie agresji; trening zastępowania agresji; cyberaggression; punishing for aggression; netiquette; the prophylaxis of the electronic aggression; aggression replacement training